2015
DOI: 10.1002/ijc.29879
|View full text |Cite
|
Sign up to set email alerts
|

Panaxydol, a component of Panax ginseng, induces apoptosis in cancer cells through EGFR activation and ER stress and inhibits tumor growth in mouse models

Abstract: We reported previously that panaxydol, a component of Panax ginseng roots, induced mitochondria-mediated apoptosis preferentially in transformed cells. This study demonstrates that EGFR activation and the resulting ER stress mediate panaxydolinduced apoptosis, and that panaxydol suppresses in vivo tumor growth in syngeneic and xenogeneic mouse tumor models. In addition, we elucidated that CaMKII and TGF-b-activated kinase (TAK1) Ginsenoside and C17 polyacetylenic compounds of Panax ginseng (P. ginseng C.A. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 42 publications
(78 reference statements)
0
42
0
Order By: Relevance
“…In addition, specific components in ginseng or ginseng-derived preparations such as compound K, ginsenoside (G) Rh1, G-F2, G-Rg3, and G-Rp1 were shown to induce apoptosis of cancer cells and were proposed to contribute to the anticancer properties of ginseng [25], [26], [27], [28], [29]. Therefore, we examined whether the antiproliferative activity of joboksansam powder involves a direct cytotoxic effect using an in vitro cell proliferation assay.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, specific components in ginseng or ginseng-derived preparations such as compound K, ginsenoside (G) Rh1, G-F2, G-Rg3, and G-Rp1 were shown to induce apoptosis of cancer cells and were proposed to contribute to the anticancer properties of ginseng [25], [26], [27], [28], [29]. Therefore, we examined whether the antiproliferative activity of joboksansam powder involves a direct cytotoxic effect using an in vitro cell proliferation assay.…”
Section: Resultsmentioning
confidence: 99%
“…The crosstalk between ER stress and ROS production is well established in cancer biology, in which increasing ROS induces ER stress to trigger cancer cell apoptosis [1113]. Interestingly, ERGR signaling plays a key role regulating ER stress and ROS accumulation [14, 15]. However, whether EGFR-mediated ER stress and ROS generation contribute to DN progression remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have proven that P. ginseng or its derived compounds show dominant effects on the various cancers using in-vivo models [53], [54]. Additionally, one study found that IR and P. ginseng also synergistically recovered the survival rate of liver cancer [55].…”
Section: Discussionmentioning
confidence: 99%